2007
DOI: 10.1073/pnas.0702424104
|View full text |Cite
|
Sign up to set email alerts
|

Circadian desynchronization of core body temperature and sleep stages in the rat

Abstract: Proper functioning of the human circadian timing system is crucial to physical and mental health. Much of what we know about this system is based on experimental protocols that induce the desynchronization of behavioral and physiological rhythms within individual subjects, but the neural (or extraneural) substrates for such desynchronization are unknown. We have developed an animal model of human internal desynchrony in which rats are exposed to artificially short (22-h) light-dark cycles. Under these conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 30 publications
6
107
0
Order By: Relevance
“…In support of this view, we have previously shown that desynchrony of sleep stages in the forced desynchronized rat emerges from the desynchrony of specific neuronal subpopulations within the SCN. 8,9 Our current findings indicate that the local circadian misalignment of neurons within the SCN circuitry, through the desynchrony of sleep stages, may impair higher cognitive functions such as long-term hippocampus memory consolidation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In support of this view, we have previously shown that desynchrony of sleep stages in the forced desynchronized rat emerges from the desynchrony of specific neuronal subpopulations within the SCN. 8,9 Our current findings indicate that the local circadian misalignment of neurons within the SCN circuitry, through the desynchrony of sleep stages, may impair higher cognitive functions such as long-term hippocampus memory consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of ECoG sleep recordings in these animals reveals that whereas NREM sleep is temporally organized according to both periodicities, REMS only exhibits a ~25-h rhythm. 8,9 The different rhythmicity of each sleep stage leads to a cycle that alternates between days in which sleep architecture (the temporal distribution of NREM and REM sleep) is similar to that of LD24 rats (aligned days, Figure 2C and 2D), and days in which wakefulness does not occur primarily during the dark phase and REM predominates in the dark phase (misaligned days, Figure 2E and 2F).…”
Section: Forced Desynchronized Rats Show Abnormal Timing Of Rem and Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence point toward the existence of multiple distinct oscillators in cells and/or tissues of organisms contributing to circadian timing. First, there exist free-running rhythms with different period lengths in the same organism (Morse et al 1994;Sai and Johnson 1999;Cambras et al 2007), and there is residual rhythmicity in strains that are defective in known oscillator components (Loros et al 1986;Stanewsky et al 1998;Emery et al 2000;Collins et al 2005). Second, some tissue-specific oscillators are constructed differently from the core oscillators located in the brain (Stanewsky et al 1998;Ivanchenko et al 2001;Krishnan et al 2001;Hardin et al 2003;Collins et al 2005).…”
Section: Introductionmentioning
confidence: 99%